2022
DOI: 10.1002/mds.29164
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants Near ZIC1 and ZIC4 in Autopsy‐Confirmed Multiple System Atrophy

Abstract: Background Multiple System Atrophy is a rare neurodegenerative disease with alpha‐synuclein aggregation in glial cytoplasmic inclusions and either predominant olivopontocerebellar atrophy or striatonigral degeneration, leading to dysautonomia, parkinsonism, and cerebellar ataxia. One prior genome‐wide association study in mainly clinically diagnosed patients with Multiple System Atrophy failed to identify genetic variants predisposing for the disease. Objective Since the clinical diagnosis of Multiple System A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Heterozygous deletions encompassing the ZIC4 locus are associated with a rare congenital cerebellar malformation known as the Dandy–Walker malformation 26 . Notably, mutations in proximity to the ZIC4 loci are implicated in multiple system atrophy, a rare neurodegenerative disease 27 . Large scale GWAS study of brain morphology has also identified associations with ZIC4 , underscoring its significance in diverse neurological processes 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Heterozygous deletions encompassing the ZIC4 locus are associated with a rare congenital cerebellar malformation known as the Dandy–Walker malformation 26 . Notably, mutations in proximity to the ZIC4 loci are implicated in multiple system atrophy, a rare neurodegenerative disease 27 . Large scale GWAS study of brain morphology has also identified associations with ZIC4 , underscoring its significance in diverse neurological processes 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Another recent GWAS study in postmortem confirmed MSA cases identified a variant in close proximity of ZIC1 and ZIC4 which encode transcription factors critical for cerebellum development. Further immunohistochemical analysis showed reduced ZIC4 -immunoreactive neurons in patients with olivopontocerebellar atrophy suggesting ZIC4 -mediated neuronal vulnerability in MSA [8].…”
Section: Geneticsmentioning
confidence: 91%